Video game design - Mandeville, Alexia (--For dummies., 2025)
"Learn what it takes to design a video game, as a hobby or as a career! Video Game Design For Dummies teaches you what it takes to design games from concept to completion. You'll learn the theory behind great gaming experiences, and you'll discover tools you can use to bring your game ideas to life. An experienced video game developer teaches you the basics of game design and how to motivate and engage players. Choose the right game engines and design tools for any project and get step-by-step advice on testing and debugging the games you've made. Thinking of pursuing game design as a career path and want to know where to start? This Dummies guide has your back. With this easy-to-understand book, you can dip your toes into the world of video game design and see where it takes you. And if you end up wanting to release your game to the masses, you'll find everything you need to know, right here. Learn the step-by-step process video game designers use to create great games. Design characters, worlds, and storylines that will keep players engaged. Pick a game engine that's right for you and plan out your game development process. Playtest your video game, then publish it and market it on social media. This book is a practical guide for beginners who want to start designing games and want to know exactly where to begin. Design a game from concept to completion, with Video Game Design for Dummies." --